Transition Experiences of Mature Students at Ontario Colleges - Jafar, Hayfa F. (Canadian Journal of Higher Education, 2023)
Drawing on 24 semi-structured interviews, this small-scale qualitative study delves into mature students’ social, academic, and career preparation experiences pursuing college education. Using Schlossberg’s (1989) transition model, the findings reveal that mature students’ overall experience is influenced by their mature status, as they possess greater confidence derived from their previous work and education experiences and the acquisition of new skills from their programs. However, some mature students perceive the career services offered by the college as being geared toward younger students, often disregarding their previous work experience. Consequently, they find these services less applicable to their needs. The transitioning-in stage for mature students is characterized by initial uncertainty that gradually transforms into a growing sense of confidence, fuelled by their experiences. These experiences motivate mature students to actively contribute to the college community by becoming mentors and assuming a supportive role for younger students during the transition-through stage. The transitioning-out for mature students involves evaluating career options and harbouring some skepticism. Nonetheless, the majority of participants expressed positive experiences and excitement about the new chapters in their lives. This study highlights the significance of tailored support and resources that acknowledge the specific needs and experiences of mature students throughout their college education.